Features of oxa-bridge cleavage in hexahydro-3a, 6-epoxyisoindol-1(4H)-ones: A concise method to access acetylisoindolones possessing anti-viral activity. Issue 43 (24th October 2019) - Zaytsev, Vladimir P.; Mertsalov, Dmitriy F.; Chervyakova, Lala V.; Krishna, Gaddam; Zubkov, Fedor I.; Dorovatovskii, Pavel V.; Khrustalev, Victor N.; Zarubaev, Vladimir V.
Graphical abstract: Highlights: Stereo- and regioselective methods for epoxy-bridge cleavage in perhydro-3a, 6-epoxyisoindolones were discovered. The reaction pathway developed is very simple and strongly depends on the characteristics of substituents. Hexahydroisoindoles display antiviral activity against the influenza virus H1N1. Abstract: Unusual stereo- and regioselective methods for epoxy-bridge cleavage in perhydro-3a, 6-epoxyisoindolones, under the action of the BF3 ·Et2 O/Ac2 O system, were discovered. The reaction pathway strongly depends on the characteristics of the isoindolone ring substituents and allows the synthesis of a wide diversity of isoindole-containing heterocycles. The obtained isoindolinones belong to a new class of anti-viral agents possessing a high activity against influenza virus A/Puerto Rico/8/34 (H1N1) in in vitro experiments.